Photocurable composition and pattern forming method

JP7645697B2Active Publication Date: 2025-03-14TOKYO OHKA KOGYO CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021071289
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-20
Publication Date
2025-03-14
Estimated Expiration
2041-04-20

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、パターン形成の際の微細パターン転写性が良好であり、並びに、硬化物における、可視光域でのヘイズ低減及び高屈折率化をより図ることができる光硬化性組成物とパターン形成方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645697000006
    Figure 0007645697000006
  • Figure 0007645697000007
    Figure 0007645697000007
  • Figure 0007645697000001
    Figure 0007645697000001
Patent Text Reader

Abstract

To provide a photocurable composition good in fine pattern-transferring property when forming a pattern, and capable of attaining haze reduction in a visible light region and a high refractive index in a cured product, and a pattern formation method.SOLUTION: A photocurable composition includes: a metal oxide nanoparticle; a (R) constituent (an unsaturated acid metal salt); a photocurable compound (excluding the (R) constituent); and a photo radical polymerization initiator. A pattern formation method includes: a process of forming a photocurable film 2 on a substrate 1 using the photocurable composition; a process of transferring an uneven pattern onto the photocurable film 2 by pressing a mold 3 having the uneven pattern onto the photocurable film 2; a process of exposing the photocurable film 2 transferred with the uneven pattern while pressing the mold 3 onto the photocurable film 2 to form a cured film; and a process of separating the mold 3 from the cured film to form a pattern 2'.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photocurable composition and a method for forming a pattern. [Background technology]

[0002] Lithography is a core technology in the manufacturing process of semiconductor devices, and in recent years, with the increasing integration density of semiconductor integrated circuits (ICs), wiring has become finer. Common methods for finer wiring include shortening the wavelength of the light source by using shorter wavelength light sources such as KrF excimer lasers, ArF excimer lasers, F2 lasers, EUV (extreme ultraviolet), EB (electron beams), and X-rays, and increasing the numerical aperture (NA) of the lens of the exposure equipment (increasing NA).

[0003] In this context, nanoimprint lithography, in which a mold having a predetermined pattern is pressed against a curable film formed on a substrate to transfer the pattern of the mold to the curable film, is gaining attention in terms of productivity, etc. as a method for forming fine semiconductor patterns. In nanoimprint lithography, a photocurable composition containing a photocurable compound that is cured by light (ultraviolet light, electron beam) is used. In this case, a mold having a predetermined pattern is pressed against a curable film containing the photocurable compound, and then the photocurable compound is cured by irradiating light, and then the mold is peeled off from the cured film to obtain a transfer pattern (structure).

[0004] The photocurable composition used in nanoimprint lithography is required to have the following properties: applicability when applied to a substrate by spin coating or the like, and curability by heating or exposure. If the applicability to the substrate is poor, the film thickness of the photocurable composition applied to the substrate varies, which tends to reduce the pattern transferability when the mold is pressed against the curable film. In addition, the curability is an important property for maintaining the pattern formed by pressing the mold to the desired dimensions. In addition, the photocurable composition is also required to have good mold releasability when the mold is peeled off from the cured film.

[0005] In recent years, the application of nanoimprint lithography has been considered to improve the functionality of 3D sensors for autonomous driving and AR (Augmented Reality) glasses. 3D sensors and AR glasses require a high refractive index for the permanent film materials that make up part of the device. One method for increasing the refractive index of nanoimprint materials is known to be the addition of metal oxide nanoparticles. For example, Patent Document 1 describes a photocurable resin composition that has a high refractive index by blending metal oxide nanoparticles such as titanium oxide or zirconium oxide. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2013-191800 A Summary of the Invention [Problem to be solved by the invention]

[0007] In order to further increase the refractive index of nanoimprint materials, it has been considered to increase the content of metal oxide nanoparticles or to increase the particle size of the metal oxide nanoparticles. However, when the content of metal oxide nanoparticles is increased to increase the refractive index, the filling of the nanoimprint pattern tends to deteriorate, resulting in a problem of reduced fine pattern transferability. Also, when the particle size of metal oxide nanoparticles is increased to increase the refractive index, the haze in the visible light region deteriorates.

[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a photocurable composition and a pattern forming method which have good fine pattern transferability during pattern formation and can further reduce haze and increase the refractive index in the visible light range in the cured product. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention employs the following configuration. That is, a first aspect of the present invention is a photocurable composition containing: component (X): metal oxide nanoparticles; component (R): an unsaturated acid metal salt; component (B): a photopolymerizable compound (excluding those corresponding to the above-mentioned component (R)); and component (C): a photoradical polymerization initiator.

[0010] A second aspect of the present invention is a pattern forming method comprising the steps of: forming a photocurable film on a substrate using the photocurable composition according to the first aspect; pressing a mold having a concave-convex pattern against the photocurable film to transfer the concave-convex pattern to the photocurable film; exposing the photocurable film to which the concave-convex pattern has been transferred while pressing the mold against the photocurable film to form a cured film; and peeling the mold from the cured film. Effect of the Invention

[0011] According to the present invention, it is possible to provide a photocurable composition and a pattern forming method which have good fine pattern transferability during pattern formation and can further reduce haze and increase the refractive index in the visible light range in the cured product. [Brief description of the drawings]

[0012] [Figure 1] 1A to 1C are schematic process diagrams illustrating an embodiment of a nanoimprint pattern formation method. [Diagram 2] FIG. 2 is a schematic process diagram illustrating an example of an optional process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In this specification and claims, the term "aliphatic" is a relative concept to aromaticity and is defined as meaning a group, compound, etc. that does not have aromaticity. Unless otherwise specified, the term "alkyl group" includes linear, branched and cyclic monovalent saturated hydrocarbon groups. The same applies to the alkyl group in an alkoxy group. "(Meth)acrylate" means at least one of acrylate and methacrylate. "(Meth)acrylic acid" means at least one of acrylic acid and methacrylic acid. The phrase "may have a substituent" includes both the case where a hydrogen atom (-H) is replaced with a monovalent group and the case where a methylene group (-CH2-) is replaced with a divalent group. The term "exposure" is intended to include the general concept of irradiation with radiation.

[0014] (Photocurable composition) The photocurable composition according to the first embodiment of the present invention contains: component (X): metal oxide nanoparticles; component (R): an unsaturated acid metal salt; component (B): a photopolymerizable compound (excluding those corresponding to the above-mentioned component (R)); and component (C): a photoradical polymerization initiator.

[0015] <(X) component> The component (X) is a metal oxide nanoparticle. "Nanoparticles" refers to particles having a volume average primary particle size on the order of nanometers (less than 1000 nm). Metal oxide nanoparticles are metal oxide particles having a volume average primary particle size on the order of nanometers. The volume average primary particle size is a value measured by a dynamic light scattering method.

[0016] The volume average primary particle diameter of component (X) is preferably 100 nm or less. The volume average primary particle diameter of component (X) is preferably 0.1 to 100 nm, more preferably 1 to 60 nm, even more preferably 1 to 50 nm, even more preferably 1 to 45 nm, and particularly preferably 1 to 40 nm. In addition, the volume average primary particle diameter of component (X) is more preferably 5 to 30 nm, 5 to 25 nm, or 5 to 30 nm. When the volume average primary particle size of the component (X) is within the above preferred range, the metal oxide nanoparticles are well dispersed in the photocurable composition, and the refractive index is also good.

[0017] As the (X) component, commercially available metal oxide nanoparticles can be used. Examples of metal oxides include oxide particles of titanium (Ti), zirconium (Zr), aluminum (Al), silicon (Si), zinc (Zn) or magnesium (Mg). Among them, as the (X) component, titania (TiO2) nanoparticles or zirconia (ZrO2) nanoparticles are preferred from the viewpoint of refractive index.

[0018] In this embodiment, commercially available metal oxide nanoparticles can be used as the component (X). Examples of commercially available titania nanoparticles include TTO series (TTO-51(A), TTO-51(C), etc.), TTO-S, V series (TTO-S-1, TTO-S-2, TTO-V-3, etc.) manufactured by Ishihara Sangyo Kaisha, Ltd.; Titaniasol LDB-014-35 manufactured by Ishihara Sangyo Kaisha, Ltd.; MT series (MT-01, MT-05, MT-100SA, MT-500SA, etc.) and NS405 manufactured by Teika Corporation; ELECOM V-9108 manufactured by JGC Catalysts and Chemicals Co., Ltd.; and STR-100A-LP manufactured by Sakai Chemical Industry Co., Ltd. Examples of commercially available zirconia nanoparticles include UEP (manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd.), UEP-100 (manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd.); PCS (manufactured by Nippon Denko Co., Ltd.); JS-01, JS-03, and JS-04 (manufactured by Nippon Denko Co., Ltd.).

[0019] In the photocurable composition of this embodiment, the component (X) may be used either as a single type alone, or as a combination of two or more types.

[0020] The content of the component (X) in the photocurable composition of this embodiment is preferably 50 to 80 parts by mass, more preferably 55 to 80 parts by mass, even more preferably 60 to 80 parts by mass, and particularly preferably 65 to 75 parts by mass, relative to 100 parts by mass of the total content of the component (X) and the later-described components (R) and (B). When the content of component (X) is equal to or greater than the lower limit of the above-mentioned preferred range, the optical properties of the cured film formed using the photocurable composition are improved, whereas when the content of component (X) is equal to or less than the upper limit of the above-mentioned preferred range, the photocurable composition is easily filled into a mold.

[0021] <(R) component> The component (R) is an unsaturated acid metal salt. The term "unsaturated acid metal salt" refers to a compound in which an anion derived from an unsaturated acid and a metal cation form an ionic bond.

[0022] The unsaturated acid is an acid having an unsaturated bond, and examples thereof include acrylic acid, methacrylic acid, crotonic acid, oleic acid, undecenoic acid, 9,12-octadienoyl acid, 9,12,15-octatrienoyl acid, etc. Among these, acrylic acid and methacrylic acid are preferred because they can easily form a film with high hardness.

[0023] Examples of metal cations include Li + , Na + , K + Alkali metal ions such as Be 2+ , Mg 2+ , Ca 2+ Alkaline earth metal ions such as Cu 2+ , Fe 3+ , Ni 2+ , Mn 2+ , Co 2+ transition metal ions such as Al 3+ , Ga 3+ , Zn 2+ , Cd 2+ Base metal ions such as Nd 3+ , Gd 3+ , Ce 3+Among these, Zn is the most popular from the viewpoints of safety and availability. 2+ , Ca 2+ , Mg 2+ , Al 3+ is preferred, Zn 2+ is particularly preferred.

[0024] Specific preferred examples of the component (R) include zinc (meth)acrylate, calcium (meth)acrylate, magnesium (meth)acrylate, and aluminum (meth)acrylate.

[0025] In this embodiment, a commercially available unsaturated acid metal salt can be used as the component (R). Examples of commercially available unsaturated acid metal salts include zinc acrylate (manufactured by Nippon Shokubai Co., Ltd.), potassium acrylate (manufactured by Nippon Shokubai Co., Ltd.), potassium methacrylate (manufactured by Nippon Shokubai Co., Ltd.); magnesium acrylate (manufactured by Asada Chemical Industry Co., Ltd.), calcium acrylate (manufactured by Asada Chemical Industry Co., Ltd.), zinc methacrylate (manufactured by Asada Chemical Industry Co., Ltd.), magnesium methacrylate (manufactured by Asada Chemical Industry Co., Ltd.), aluminum acrylate (manufactured by Asada Chemical Industry Co., Ltd.), neodymium methacrylate (manufactured by Asada Chemical Industry Co., Ltd.), sodium methacrylate (manufactured by Asada Chemical Industry Co., Ltd.), and potassium acrylate (manufactured by Asada Chemical Industry Co., Ltd.).

[0026] In the photocurable composition of this embodiment, the component (R) may be used either as a single type alone, or as a combination of two or more types. Among the (R) components, zinc (meth)acrylate is preferred, and zinc acrylate is particularly preferred, since it is likely to enhance the effects of the present invention.

[0027] The content of the (R) component in the photocurable composition of this embodiment is preferably 1 to 30 parts by mass, more preferably 1 to 25 parts by mass, and even more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the total content of the (X) component, the (R) component, and the (B) component. When the content of the (R) component is equal to or greater than the lower limit of the above-mentioned preferred range, the haze in the visible light region of the cured film formed using the photocurable composition is more likely to be reduced. Also, the strength of the cured film is more improved. On the other hand, when the content of the (R) component is equal to or less than the upper limit of the above-mentioned preferred range, the refractive index of the cured film formed using the photocurable composition is more likely to be increased.

[0028] <(B) component> The component (B) is a photopolymerizable compound (excluding those corresponding to the component (R) above). The photopolymerizable compound refers to a compound having a polymerizable functional group. The term "polymerizable functional group" refers to a group that enables compounds to polymerize together by radical polymerization or the like, and is, for example, a group that contains a multiple bond between carbon atoms, such as an ethylenic double bond.

[0029] Examples of the polymerizable functional group include vinyl group, allyl group, acryloyl group, methacryloyl group, fluorovinyl group, difluorovinyl group, trifluorovinyl group, difluorotrifluoromethylvinyl group, trifluoroallyl group, perfluoroallyl group, trifluoromethylacryloyl group, nonylfluorobutylacryloyl group, vinyl ether group, fluorine-containing vinyl ether group, allyl ether group, fluorine-containing allyl ether group, styryl group, vinylnaphthyl group, fluorine-containing styryl group, fluorine-containing vinylnaphthyl group, norbornyl group, fluorine-containing norbornyl group, and silyl group. Among these, vinyl group, allyl group, acryloyl group, and methacryloyl group are preferred, and acryloyl group and methacryloyl group are more preferred.

[0030] Examples of photopolymerizable compounds (monofunctional monomers) having one polymerizable functional group include (meth)acrylates containing an aliphatic polycyclic structure such as isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, bornyl (meth)acrylate, and tricyclodecanyl (meth)acrylate; (meth)acrylates containing an aliphatic monocyclic structure such as dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, cyclohexyl (meth)acrylate, 4-butylcyclohexyl (meth)acrylate, and acryloylmorpholine; 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and methyl (meth)acrylate. (meth)acrylates having a chain structure, such as acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and isostearyl (meth)acrylate;Benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy-2-methylethyl (meth)acrylate, phenoxyethoxyethyl (meth)acrylate, 3-phenoxy-2-hydroxypropyl (meth)acrylate, 2-phenylphenoxyethyl (meth)acrylate, 4-phenylphenoxyethyl (meth)acrylate, 3-(2-phenylphenyl)-2-hydroxypropyl (meth)acrylate, EO-modified p-cumylphenol (meth)acrylate, 2-bromophenoxyethyl (meth)acrylate, 2,4-dibromophenoxyethyl (meth)acrylate, 2,4,6-tribromophenoxyethyl (meth)acrylate, EO-modified phenoxy (meth)acrylate, PO-modified phenoxy (meth)acrylate, polyoxyethylene nonylphenyl ether (meth)acrylate, and other aromatic ring structure-containing (meth)acrylates; tetrahydrofurfuryl (meth) Acrylate, butoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, methoxyethylene glycol (meth)acrylate, ethoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate; diacetone (meth)acrylamide, isobutoxymethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, t-octyl (meth)acrylamide, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 7-amino-3,7-dimethyloctyl (meth)acrylate, N,N-diethyl (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylamide; one-terminated methacrylsiloxane monomer, etc.;

[0031] Commercially available products of the monofunctional monomer include, for example, ARONIX M101, M102, M110, M111, M113, M117, M5700, TO-1317, M120, M150, and M156 (all manufactured by Toagosei Co., Ltd.); MEDOL10, MIBDOL10, CHDOL10, MMDOL30, MEDOL30, MIBDOL30, CHDOL30, LA, IBXA, 2-MTA, HPA, and Viscoat #150 and #155. , #158, #190, #192, #193, #220, #2000, #2100, #2150 (all manufactured by Osaka Organic Chemical Industry Co., Ltd.); Light acrylate BO-A, EC-A, DMP-A, THF-A, HOP-A, HOA-MPE, HOA-MPL, HOA(N), PO-A, P-200A, NP-4EA, NP-8EA, IB-XA, Epoxy ester M-600A (all manufactured by Kyoeisha Chemical Co., Ltd.); KAYARAD Examples of such compounds include TC110S, R-564, and R-128H (all manufactured by Nippon Kayaku Co., Ltd.); NK Ester AMP-10G and AMP-20G (all manufactured by Shin-Nakamura Chemical Co., Ltd.); FA-511A, FA-512A, FA-513A, and FA-BZA (all manufactured by Hitachi Chemical Co., Ltd.); PHE, CEA, PHE-2, PHE-4, BR-31, BR-31M, and BR-32 (all manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.); VP (manufactured by BASF); ACMO, DMAA, and DMAPAA (all manufactured by Kohjin Co., Ltd.); and X-22-2404 (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0032] Examples of photopolymerizable compounds having two polymerizable functional groups (bifunctional monomers) include trimethylolpropane di(meth)acrylate, ethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, bis(hydroxymethyl)tricyclodecane di(meth)acrylate, and the like.

[0033] Commercially available bifunctional monomers include, for example, Light Acrylate 3EG-A, 4EG-A, 9EG-A, NP-A, DCP-A, BP-4EAL, and BP-4PA (all manufactured by Kyoeisha Chemical Co., Ltd.).

[0034] Examples of the photopolymerizable compound having three or more polymerizable functional groups include a photopolymerizable siloxane compound, a photopolymerizable silsesquioxane compound, and a polyfunctional monomer having three or more polymerizable functional groups.

[0035] Examples of the photopolymerizable siloxane compound include compounds having an alkoxysilyl group and a polymerizable functional group in the molecule. Commercially available examples of the photopolymerizable siloxane compound include those manufactured by Shin-Etsu Chemical Co., Ltd. under the product names "KR-513", "X-40-9296", "KR-511", "X-12-1048", and "X-12-1050".

[0036] The photopolymerizable silsesquioxane compound has a main chain structure composed of Si-O bonds and has the following chemical formula: [(RSiO 3 / 2 ) n

[0033] (wherein R represents an organic group, and n represents a natural number). R represents a monovalent organic group, and the monovalent organic group may be a monovalent hydrocarbon group which may have a substituent. The hydrocarbon group may be an aliphatic hydrocarbon group or an aromatic hydrocarbon group. The aliphatic hydrocarbon group may be an alkyl group having 1 to 20 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, a 2-ethylhexyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, or a dodecyl group, and an alkyl group having 1 to 12 carbon atoms is preferred. Examples of the aromatic hydrocarbon group include aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, a benzyl group, a tolyl group, and a styryl group. Examples of the substituent that the monovalent hydrocarbon group may have include a (meth)acryloyl group, a hydroxy group, a sulfanyl group, a carboxy group, an isocyanato group, an amino group, a ureido group, etc. In addition, -CH2- contained in the monovalent hydrocarbon group may be replaced with -O-, -S-, a carbonyl group, etc. However, the photopolymerizable silsesquioxane compound has three or more polymerizable functional groups, such as vinyl groups, allyl groups, methacryloyl groups, and acryloyl groups.

[0037] Chemical formula: [(RSiO 3 / 2 ) n The compound represented by the formula (I) may be any of a cage type, a ladder type, and a random type. The cage type silsesquioxane compound may be a complete cage type or an incomplete cage type in which the cage is partially open.

[0038] Commercially available examples of the photopolymerizable silsesquioxane compound include those manufactured by Toagosei Co., Ltd. under the product names "MAC-SQ LP-35," "MAC-SQ TM-100," "MAC-SQ SI-20," and "MAC-SQ HDM."

[0039] Examples of polyfunctional monomers having three or more polymerizable functional groups include ethoxylated (3) trimethylolpropane triacrylate, ethoxylated (3) trimethylolpropane trimethacrylate, ethoxylated (6) trimethylolpropane triacrylate, ethoxylated (9) trimethylolpropane triacrylate, ethoxylated (15) trimethylolpropane triacrylate, ethoxylated (20) trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, propoxylated (3) glyceryl triacrylate, propoxylated (3) glyceryl triacrylate, propoxylated (5.5) glyceryl triacrylate, propoxylated (3) trimethylolpropane triacrylate, propoxylated (6) trimethylolpropane triacrylate, trimethylolpropane triacrylate, trifunctional monomers such as propylene triacrylate, trimethylolpropane trimethacrylate, tris-(2-hydroxyethyl)-isocyanurate triacrylate, tris-(2-hydroxyethyl)-isocyanurate trimethacrylate, ε-caprolactone modified tris-(2-acryloxyethyl)isocyanurate, EO modified trimethylolpropane tri(meth)acrylate, PO modified trimethylolpropane tri(meth)acrylate, EO,PO modified trimethylolpropane tri(meth)acrylate; tetrafunctional monomers such as ditrimethylolpropane tetraacrylate, ethoxylated (4) pentaerythritol tetraacrylate, pentaerythritol tetra(meth)acrylate; and pentafunctional or higher monomers such as dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate.

[0040] Commercially available examples of the polyfunctional monomer include those manufactured by Shin-Nakamura Chemical Co., Ltd. under the product names "A-9300-1CL," "AD-TMP," "A-9550," and "A-DPH," those manufactured by Nippon Kayaku Co., Ltd. under the product name "KAYARAD DPHA," and those manufactured by Kyoeisha Chemical Co., Ltd. under the product name "Light Acrylate TMP-A." In addition, as the component (B), commercially available products other than those mentioned above, for example, products under the names "NK Oligo EA-1010NT2" and "NK Ester A-BPML" manufactured by Shin-Nakamura Chemical Co., Ltd., can also be used.

[0041] The (B) component may be a photopolymerizable sulfur compound (hereinafter also referred to as the (BS) component). The "photopolymerizable sulfur compound" is a photopolymerizable compound containing a sulfur atom in the molecule. That is, the photopolymerizable sulfur compound is a monomer containing a sulfur atom and having a polymerizable functional group.

[0042] The (BS) component may, for example, be a compound having a diaryl sulfide skeleton. The compound having a diaryl sulfide skeleton may, for example, be a compound represented by the following general formula (bs-1).

[0043] [ka] [In the formula, R 11 ~R 14 and R 21 ~R 24 each independently represents a hydrogen atom, an alkyl group, or a halogen atom; R 5 represents a polymerizable functional group.

[0044] In the above formula (bs-1), R 11 ~R 14 and R 21 ~R 24 each independently represents a hydrogen atom, an alkyl group, or a halogen atom. The alkyl group preferably has 1 to 10 carbon atoms, more preferably has 1 to 6 carbon atoms, further preferably has 1 to 4 carbon atoms, and particularly preferably has 1 to 3 carbon atoms. The alkyl group may be linear, branched, or cyclic, and is preferably linear or branched. Examples of the linear alkyl group include a methyl group, an ethyl group, an n-propyl group, an n-butyl group, etc. Examples of the branched alkyl group include an isopropyl group, a sec-butyl group, a tert-butyl group, etc. Among them, the alkyl group is preferably a methyl group or an ethyl group, and more preferably a methyl group.

[0045] R 11 ~R 14 and R 21 ~R 24 Examples of the halogen atom in include a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc. The halogen atom is preferably a chlorine atom.

[0046] R 11 ~R 14 and R 21 ~R 24 is preferably a hydrogen atom or an alkyl group, more preferably a hydrogen atom, a methyl group or an ethyl group, and further preferably a hydrogen atom.

[0047] In the above formula (bs-1), R 5 represents a polymerizable functional group. Examples of the polymerizable functional group include the same groups as those listed above. Among them, the polymerizable functional group is preferably a vinyl group, an allyl group, an acryloyl group, or a methacryloyl group, and more preferably an acryloyl group or a methacryloyl group. R 5 is preferably an acryloyl group or a methacryloyl group, and more preferably an acryloyl group or a methacryloyl group.

[0048] Examples of the (BS) component include bis(4-methacryloylthiophenyl)sulfide and bis(4-acryloylthiophenyl)sulfide. Of these, the (BS) component is preferably bis(4-methacryloylthiophenyl)sulfide.

[0049] In the photocurable composition of this embodiment, the component (B) may be used either as a single type alone, or as a combination of two or more types. The component (B) preferably contains a polyfunctional monomer having three or more polymerizable functional groups. By containing such a polyfunctional monomer, the refractive index of the cured film formed using the photocurable composition is further improved.

[0050] The content of the (B) component in the photocurable composition of this embodiment is preferably 1 to 30 parts by mass, more preferably 2 to 30 parts by mass, and even more preferably 3 to 30 parts by mass, relative to 100 parts by mass of the total content of the (X) component, the (R) component, and the (B) component. When the content of component (B) is equal to or greater than the lower limit of the above-mentioned preferred range, the curing property and fluidity of the cured resin film formed using the photocurable composition are improved. On the other hand, when the content of component (B) is equal to or less than the upper limit of the above-mentioned preferred range, the dispersibility of each of components (X) and (R) in the photocurable composition is improved.

[0051] In the photocurable composition of this embodiment, relative to 100 parts by mass of the total content of the (X) component, the (R) component, and the (B) component, it is preferable that the content of the (R) component is 1 to 30 parts by mass and the content of the (B) component is 1 to 30 parts by mass, it is more preferable that the content of the (R) component is 1 to 25 parts by mass and the content of the (B) component is 2 to 30 parts by mass, and it is even more preferable that the content of the (R) component is 1 to 20 parts by mass and the content of the (B) component is 3 to 30 parts by mass.

[0052] <(C) component> The component (C) is a photoradical polymerization initiator. As the component (C), a compound that initiates or promotes polymerization of the components (R) and (B) upon exposure to light is used.

[0053] Examples of the component (C) include 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropan-1-one, 2,2-dimethoxy-1,2-diphenylethane-1-one, bis(4-dimethylaminophenyl)ketone, 2- Methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, ethanone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(o-acetyloxime), bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 4-benzoyl-4'-methyldimethylsulfide, 4-dimethylaminobenzoic acid, methyl 4-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate , butyl 4-dimethylaminobenzoate, 4-dimethylamino-2-ethylhexylbenzoic acid, 4-dimethylamino-2-isoamylbenzoic acid, benzyl-β-methoxyethyl acetal, benzyl dimethyl ketal, 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, methyl o-benzoylbenzoate, 2,4-diethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 1-chloro-4-propoxythioxanthone, thioxanthene, 2-chlorothioxanthene, 2,4-diethyl Thioxanthene, 2-methylthioxanthene, 2-isopropylthioxanthene, 2-ethylanthraquinone, octamethylanthraquinone, 1,2-benzanthraquinone, 2,3-diphenylanthraquinone, azobisisobutyronitrile, benzoyl peroxide, cumene peroxide, 2-mercaptobenzimidazole, 2-mercaptobenzoxazole, 2-mercaptobenzothiazole, 2-(o-chlorophenyl)-4,5-di(m-methoxyphenyl)-imidazolyl dimer, benzophenone, 2-chlorobenzophenone, p,p'-Bisdimethylaminobenzophenone, 4,4'-Bisdiethylaminobenzophenone, 4,4'-Dichlorobenzophenone, 3,3-Dimethyl-4-methoxybenzophenone, Benzoyl, Benzoin, Benzoin methyl ether, Benzoin ethyl ether, Benzoin isopropyl ether, Benzoin-n-butyl ether, Benzoin isobutyl ether, Benzoin butyl ether, Acetophenone, 2,2-Diethoxyacetophenone, p-Dimethylacetophenone, p-Dimethylaminopropiophenone, Dichloroacetophenone acetophenone, trichloroacetophenone, p-tert-butylacetophenone, p-dimethylaminoacetophenone, p-tert-butyltrichloroacetophenone, p-tert-butyldichloroacetophenone, α,α-dichloro-4-phenoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, thioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, dibenzosuberone, pentyl-4-dimethylaminobenzoate, 9-phenylacridine, 1,7-bis-(9-acridinyl)heptane , 1,5-bis-(9-acridinyl)pentane, 1,3-bis-(9-acridinyl)propane, p-methoxytriazine, 2,4,6-tris(trichloromethyl)-s-triazine, 2-methyl-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(5-methylfuran-2-yl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(furan-2-yl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(4-diethylamino-2-methylphenyl)ethenyl]- 4,6-bis(trichloromethyl)-s-triazine, 2-[2-(3,4-dimethoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-ethoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-n-butoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis-trichloromethyl-6-(3-bromo-4-methoxy)phenyl-s-triazine, 2,4-Bis-trichloromethyl-6-(2-bromo-4-methoxy)phenyl-s-triazine, 2,4-bis-trichloromethyl-6-(3-bromo-4-methoxy)styrylphenyl-s-triazine, 2,4-bis-trichloromethyl-6-(2-bromo-4-methoxy)styrylphenyl-s-triazine; ketone peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, and cyclohexanone peroxide; diacyl peroxides such as isobutyryl peroxide and bis(3,5,5-trimethylhexanoyl) peroxide; p-menthane hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide Examples of peroxy compounds include hydroperoxides such as cyclohexyl ether, dialkyl peroxides such as 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, peroxyketals such as 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, peroxyesters such as t-butylperoxyneodecanoate and 1,1,3,3-tetramethylperoxyneodecanoate, peroxydicarbonates such as di-n-propylperoxydicarbonate and diisopropylperoxydicarbonate, and azo compounds such as azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobisisobutyrate.

[0054] Among the above, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and 2,2-dimethoxy-2-phenylacetophenone are preferred.

[0055] As the component (C), a commercially available product can be used. Commercially available products of component (C) include products manufactured by BASF under the names "IRGACURE 907", "IRGACURE 369", and "IRGACURE 819"; and products manufactured by IGM Resins BV under the names "Omnirad 184", "Omnirad 651", "Omnirad 819", and "Omnirad 184".

[0056] The molecular weight of the (C) component is preferably small. When the molecular weight of the (C) component is small, the haze tends to be further reduced. The molecular weight of the (C) component is, for example, preferably 500 or less, more preferably 400 or less, even more preferably 350 or less, and particularly preferably 300 or less. The lower limit of the molecular weight of the (C) component is not particularly limited, but may be 100 or more, 150 or more, or 200 or more. The molecular weight of the (C) component may be, for example, 100 to 500, preferably 150 to 500, more preferably 150 to 400, even more preferably 150 to 350, and particularly preferably 150 to 300.

[0057] In the photocurable composition of this embodiment, the component (C) may be used either as a single type alone, or as a combination of two or more types.

[0058] The content of the (C) component in the photocurable composition of this embodiment is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, and even more preferably 5 to 15 parts by mass, relative to 100 parts by mass of the total content of the (X) component, the (R) component, and the (B) component. When the content of component (C) is equal to or greater than the lower limit of the preferred range, it is easy to reduce haze while maintaining a high refractive index, whereas when the content of component (C) is equal to or less than the upper limit of the preferred range, it is possible to satisfactorily maintain a high refractive index.

[0059] <Optional ingredients> The photocurable composition according to the embodiment may contain, in addition to the components (X), (R), (B) and (C), other components (optional components). Examples of such optional components include a solvent (component (S)), a surfactant (component (E)), and compatible additives (e.g., anti-degradants, release agents, diluents, antioxidants, heat stabilizers, flame retardants, plasticizers, and other additives for improving the properties of the cured film).

[0060] <Solvent: (S) component> The photocurable composition of this embodiment may contain a solvent (component (S)). The component (S) is used to dissolve or disperse and mix the above-mentioned components (X), (R), (B), and (C) and any desired optional components.

[0061] Examples of the (S) component include methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-pentyl alcohol, s-pentyl alcohol, t-pentyl alcohol, isopentyl alcohol, 2-methyl-1-propanol, 2-ethylbutanol, neopentyl alcohol, n-butanol, s-butanol, t-butanol, 1-propanol, n-hexanol, 2-heptanol, 3-heptanol, 2-methyl-1-butanol, 2-methyl -2-butanol, 4-methyl-2-pentanol, 1-butoxy-2-propanol, propylene glycol monopropyl ether, 5-methyl-1-hexanol, 6-methyl-2-heptanol, 1-octanol, 2-octanol, 3-octanol, 4-octanol, 2-ethyl-1-hexanol, 2-(2-butoxyethoxy)ethanol and other chain alcohols; cyclopentanemethanol, 1-cyclopentylethanol, cyclohexanol, cyclo Examples of the alcohols include alcohols having a cyclic structure such as hexanemethanol, cyclohexaneethanol, 1,2,3,6-tetrahydrobenzyl alcohol, exo-norborneol, 2-methylcyclohexanol, cycloheptanol, 3,5-dimethylcyclohexanol, benzyl alcohol, and terpineol; compounds having an ester bond such as ethylene glycol monoacetate, diethylene glycol monoacetate, propylene glycol monoacetate, and dipropylene glycol monoacetate; derivatives of polyhydric alcohols such as monoalkyl ethers, monomethyl ethers, monoethyl ethers, monopropyl ethers, and monobutyl ethers of the polyhydric alcohols or compounds having an ester bond, or compounds having an ether bond such as monophenyl ethers [among these, propylene glycol monomethyl ether acetate (PGMEA) and propylene glycol monomethyl ether (PGME) are preferred].

[0062] In the photocurable composition of this embodiment, the component (S) may be used either as a single type alone, or as a combination of two or more types. Among the above, the component (S) is preferably at least one selected from the group consisting of propylene glycol monomethyl ether acetate (PGMEA) and propylene glycol monomethyl ether (PGME).

[0063] The amount of the (S) component used is not particularly limited and may be appropriately determined depending on the coating thickness of the photocurable composition. For example, the (S) component may be used in an amount of about 100 to 500 parts by mass per 100 parts by mass of the total amount of the (X) component, the (R) component, and the (B) component.

[0064] <Surfactant: Component (E)> The photocurable composition of this embodiment may contain a surfactant (component (E)) in order to adjust the coatability and the like. Examples of the component (E) include silicone-based surfactants and fluorine-based surfactants. Examples of silicone surfactants that can be used include BYK-077, BYK-085, BYK-300, BYK-301, BYK-302, BYK-306, BYK-307, BYK-310, BYK-320, BYK-322, BYK-323, BYK-325, BYK-330, BYK-331, BYK-333, BYK-335, BYK-341, BYK-344, BYK-345, BYK-346, BYK-348, BYK-354, BYK-355, BYK-356, BYK-358, BYK-361, BYK-370, BYK-371, BYK-375, BYK-380, and BYK-390 (all manufactured by BYK Chemie). Examples of fluorine-based surfactants include F-114, F-177, F-410, F-411, F-450, F-493, F-494, F-443, F-444, F-445, F-446, F-470, F-471, F-472SF, F-474, F-475, F-477, F-478, F-479, F-480SF, F-482, F-483, F-484, F-486, F-487, F-172D, MCF-350SF, and TF-10. 25SF, TF-1117SF, TF-1026SF, TF-1128, TF-1127, TF-1129, TF-1126, TF-1130, TF-1116SF, TF-1131, TF-1132, TF-1027SF, TF-1441, TF-1442 (all manufactured by DIC Corporation); Polyfox series PF-636, PF-6320, PF-656, PF-6520 (all manufactured by Omnova), etc. can be used.

[0065] In the photocurable composition of this embodiment, the component (E) may be used either as a single type alone, or as a combination of two or more types. When the photocurable composition of this embodiment contains the component (E), the content of the component (E) is preferably 0.01 to 3 parts by mass, more preferably 0.02 to 1 part by mass, and even more preferably 0.03 to 0.5 parts by mass, relative to 100 parts by mass of the total content of the component (X), the component (R), and the component (B). When the content of the component (E) is within the above preferred range, the coatability of the photocurable composition is good.

[0066] A cured film formed using the photocurable composition of this embodiment usually has a refractive index of 1.70 or more at a wavelength of 530 nm, and the refractive index is preferably 1.75 or more. The photocurable composition of this embodiment can form a cured film with such a high refractive index, and therefore can be suitably used in applications requiring a high refractive index, such as 3D sensors and AR waveguides in AR (augmented reality) glasses. The refractive index of the cured film can be measured by a spectroscopic ellipsometer.

[0067] A 600 nm thick cured film formed using the photocurable composition of this embodiment typically has a haze value of 0.1% or less as measured in accordance with ASTM D1003. The photocurable composition of this embodiment can form a cured film with such a low haze value, and therefore can be suitably used for applications requiring high transparency, such as 3D sensors and AR waveguides in AR (augmented reality) glasses. The haze value of the cured film can be measured using a haze meter in accordance with ASTM D1003.

[0068] The photocurable composition of the present embodiment described above contains (X) component: metal oxide nanoparticles, (R) component: unsaturated acid metal salt, (B) component: photopolymerizable compound (excluding those corresponding to the above-mentioned (R) component), and (C) component: photoradical polymerization initiator. In the photocurable composition of the present embodiment, the (R) component is used in combination with the (X) component and the (B) component, so that the fine pattern transferability during pattern formation is good, and the haze reduction and high refractive index in the visible light region of the cured product can be further achieved.

[0069] In a nanoimprint process, the finer and more complicated the pattern, the greater the stress generated in the imprint material when it is released from the mold. In the photocurable composition of this embodiment, the (R) component is used in combination to increase the resistance to the stress. This improves mold releasability, and improves the transferability of fine patterns during pattern formation. In addition, in the photocurable composition of the present embodiment, by combining the (R) component and the (B) component, the film density is increased by metal ion bonds in the photocurable film compared to a photocurable film formed from the (B) component alone, and therefore the refractive index of the cured product is increased. In addition, by combining the (X), (R) and (B) components, the refractive index difference at the interface between the metal oxide nanoparticles and the binder resin becomes smaller, which suppresses the light scattering phenomenon at the interface and reduces the haze in the visible light range in the cured product. In this way, the photocurable composition of this embodiment can solve a problem that was previously difficult to solve, that is, the trade-off problem between the deterioration of fine pattern transferability and the increase in haze of the cured product that accompanies an increase in the refractive index of the cured product. By applying the photocurable composition of this embodiment, fine pattern transferability during pattern formation is good, and a fine pattern can be easily formed in which the refractive index of the cured film at a wavelength of 530 nm is 1.70 or more and the haze value of the cured film with a thickness of 600 nm is 0.1% or less.

[0070] Such photocurable compositions are useful as materials for forming fine patterns on substrates by imprint technology, and are particularly suitable for photoimprint lithography, and are particularly advantageous in applications requiring high refractive index and low haze, such as 3D sensors for autonomous driving and AR waveguides for augmented reality (AR) glasses. The photocurable composition of this embodiment is also useful as a material for an anti-reflection film, for example.

[0071] (Pattern formation method) The pattern forming method of the second embodiment of the present invention includes a step of forming a photocurable film on a substrate using the photocurable composition of the first embodiment described above (hereinafter referred to as "step (i)"); a step of pressing a mold having a concave-convex pattern against the photocurable film to transfer the concave-convex pattern to the photocurable film (hereinafter referred to as "step (ii)"); a step of exposing the photocurable film to which the concave-convex pattern has been transferred while pressing the mold against the photocurable film to form a cured film (hereinafter referred to as "step (iii)"); and a step of peeling the mold from the cured film (hereinafter referred to as "step (iv)").

[0072] FIG. 1 is a schematic process diagram illustrating one embodiment of a pattern forming method.

[0073] [Step (i)] In the step (i), a photocurable film is formed on a substrate using the photocurable composition of the first embodiment described above. As shown in Fig. 1(A), the photocurable composition of the first embodiment described above is applied to a substrate 1 to form a photocurable film 2. In Fig. 1(A), a mold 3 is disposed above the photocurable film 2.

[0074] The substrate 1 can be selected according to various applications, and examples thereof include a substrate for electronic components, a substrate on which a predetermined wiring pattern is formed, etc. More specifically, examples thereof include substrates made of metals such as silicon, silicon nitride, copper, chromium, iron, and aluminum, and glass substrates. Examples of materials for the wiring pattern include copper, aluminum, nickel, and gold. The shape of the substrate 1 is not particularly limited, and may be a plate or a roll. The substrate 1 may be either light-transmitting or non-light-transmitting depending on the combination with the mold.

[0075] Methods for applying the photocurable composition to the substrate 1 include spin coating, spraying, ink-jet, roll coating, and rotary coating. Since the photocurable film 2 functions as a mask in a subsequent etching step of the substrate 1, it is preferable that the film thickness is uniform when applied to the substrate 1. From this viewpoint, when applying the photocurable composition to the substrate 1, a spin coating method is suitable. The thickness of the photocurable film 2 may be appropriately selected depending on the application, and may be, for example, about 0.05 to 30 μm.

[0076] [Step (ii)] In the step (ii), a mold having a concave-convex pattern is pressed against the photocurable film to transfer the concave-convex pattern to the photocurable film. 1(B), a mold 3 having a fine uneven pattern on its surface is pressed against the substrate 1 on which the photocurable film 2 is formed, so as to face the photocurable film 2. This causes the photocurable film 2 to deform in accordance with the uneven structure of the mold 3.

[0077] The pressure applied to the photocurable film 2 when the mold 3 is pressed is preferably 10 MPa or less, more preferably 5 MPa or less, and particularly preferably 1 MPa or less. By pressing the mold 3 against the photocurable film 2, the photocurable composition located on the convex parts of the mold 3 is easily pushed away to the concave parts of the mold 3, and the uneven structure of the mold 3 is transferred to the photocurable film 2.

[0078] The concave-convex pattern of the mold 3 can be formed according to a desired processing accuracy by, for example, photolithography or electron beam lithography. The mold 3 is preferably a light-transmitting mold. The material of the light-transmitting mold is not particularly limited, but may be any material having a predetermined strength and durability. Specific examples include glass, quartz, light-transmitting resin films such as polymethyl methacrylate and polycarbonate resin, transparent metal deposition films, flexible films such as polydimethylsiloxane, photocured films, metal films, and the like.

[0079] [Step (iii)] In the step (iii), the photocurable film to which the concave-convex pattern has been transferred is exposed to light while the mold is pressed against the photocurable film to form a cured resin film. 1(C), while the mold 3 is pressed against the photocurable film 2, the photocurable film 2 to which the concave-convex pattern has been transferred is exposed to light. Specifically, electromagnetic waves such as ultraviolet (UV) rays are irradiated onto the photocurable film 2. By exposure, the photocurable film 2 is cured while the mold 3 is pressed against it, and a cured film (cured pattern) to which the concave-convex pattern of the mold 3 has been transferred is formed. It should be noted that the mold 3 in FIG. 1(C) is transparent to electromagnetic waves.

[0080] The light used to cure the photocurable film 2 is not particularly limited, and examples thereof include light or radiation with wavelengths in the range of high-energy ionizing radiation, near ultraviolet light, far ultraviolet light, visible light, infrared light, etc. As the radiation, for example, microwaves, EUV, LED, semiconductor laser light, or laser light used in semiconductor microfabrication such as 248 nm KrF excimer laser light or 193 nm ArF excimer laser light can be suitably used. These lights may be monochrome light or may be light with multiple different wavelengths (mixed light).

[0081] [Step (iv)] In step (iv), the mold is peeled off from the cured film. 1(D), the mold 3 is peeled off from the cured film. As a result, a pattern 2′ (cured pattern) made of the cured film to which the concave-convex pattern has been transferred is patterned on the substrate 1.

[0082] In the pattern forming method of the present embodiment described above, a photocurable composition containing the above-mentioned components (X), (R), (B) and (C) is used. The use of such a photocurable composition provides good fine pattern transferability during pattern formation, and allows the formation of a pattern having a high refractive index and reduced haze in the visible light region.

[0083] In this embodiment, a release agent may be applied to a surface 31 of the mold 3 that comes into contact with the photocurable film 2 (FIG. 1(A)). This enhances the releasability between the mold and the cured film. Examples of the release agent include silicon-based release agents, fluorine-based release agents, polyethylene-based release agents, polypropylene-based release agents, paraffin-based release agents, montan-based release agents, and carnauba-based release agents. Among these, fluorine-based release agents are preferred. For example, commercially available coating-type release agents such as Optool DSX manufactured by Daikin Industries, Ltd. can be suitably used. The release agent may be used alone or in combination of two or more types.

[0084] In this embodiment, an organic layer may be provided between the substrate 1 and the photocurable film 2. This allows a desired pattern to be easily and reliably formed on the substrate 1 by etching the substrate 1 using the photocurable film 2 and the organic layer as a mask. The thickness of the organic layer may be adjusted appropriately depending on the depth to which the substrate 1 is processed (etched), and is preferably, for example, 0.02 to 2.0 μm. The material of the organic layer is preferably one that has lower etching resistance to oxygen-based gases than the photocurable composition, and has higher etching resistance to halogen-based gases than the substrate 1. The method for forming the organic layer is not particularly limited, and examples thereof include a sputtering method and a spin coating method.

[0085] The pattern formation method of the second embodiment may further include other steps (optional steps) in addition to the steps (i) to (iv). Examples of the optional steps include an etching step (step (v)) and a step of removing the cured film (cured pattern) after the etching treatment (step (vi)).

[0086] [Process (v)] In step (v), for example, the substrate 1 is etched using the pattern 2' obtained in the above steps (i) to (iv) as a mask. As shown in FIG. 2(E), the substrate 1 on which the pattern 2' is formed is irradiated with at least one of plasma and reactive ions (indicated by the arrows), so that the portion of the substrate 1 exposed on the side of the pattern 2' is etched away to a predetermined depth. The plasma or reactive ion gas used in step (v) is not particularly limited as long as it is a gas commonly used in the field of dry etching.

[0087] [Process (vi)] In step (vi), the cured film remaining after the etching treatment in step (v) is removed. As shown in FIG. 2(F), this is a step of removing the cured film (pattern 2') remaining on the substrate 1 after the etching treatment of the substrate 1. The method for removing the cured film (pattern 2') remaining on the substrate 1 is not particularly limited, but may be, for example, a treatment for washing the substrate 1 with a solution that dissolves the cured film. EXAMPLES

[0088] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0089] <Preparation of Photocurable Composition> (Examples 1 to 12, Comparative Examples 1 to 16) The components shown in Tables 1 and 2 were mixed to prepare photocurable compositions of each example.

[0090] [Table 1]

[0091] [Table 2]

[0092] In Tables 1 and 2, the abbreviations have the following meanings: The numbers in brackets [ ] are the blend amounts (parts by mass).

[0093] Component (X) (metal oxide nanoparticles) (X)-1: Titania particles, manufactured by Teika Corporation, product name "NS405". Volume average primary particle diameter: 15 nm. (X)-2: Titania particles, manufactured by JGC Catalysts & Chemicals Co., Ltd., product name "ELECOM V-9108". Volume average primary particle diameter 15nm. (X)-3: Zirconia particles, manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd., product name "UEP-100". Volume average primary particle diameter: 15 nm.

[0094] (R) Component (unsaturated acid metal salt) (R)-1: Zinc acrylate, manufactured by Nippon Shokubai Co., Ltd., product name "ZN-DA100".

[0095] ·(B) Component (photopolymerizable compound) (B)-1: Multifunctional acrylate, manufactured by Nippon Kayaku Co., Ltd., product name "KAYARAD DPHA". (B)-2: Trimethylolpropane triacrylate, manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Acrylate TMP-A".

[0096] (B)-3: Bisphenol A type epoxy acrylate, manufactured by Shin-Nakamura Chemical Co., Ltd., product name "NK Oligo EA-1010NT2". (B)-4: Product name "NK Ester A-BPML", manufactured by Shin-Nakamura Chemical Co., Ltd.

[0097] Component (C) (photoradical polymerization initiator) (C)-1: 2,2-Dimethoxy-2-phenylacetophenone, manufactured by IGM Resins BV, product name "Omnirad 651". Molecular weight: 256.3.

[0098] Component (E) (surfactant) (E)-1: Fluorosurfactant, manufactured by OMNOVA, product name "PolyFox PF656".

[0099] (S) component (solvent) (S)-1: Propylene glycol monomethyl ether acetate (PGMEA) (S)-2: Propylene glycol monomethyl ether (PGME)

[0100] <Evaluation> For each example of the photocurable composition, the imprint transferability, the refractive index and the haze of the cured film were evaluated by the methods described below. The results are shown in Tables 3 to 4.

[0101] [Imprint transferability] The photocurable composition was spin-coated on a silicon substrate to a thickness of 600 nm, and then pre-baked at 100° C. for 1 minute. Using an imprinting device ST-200 manufactured by Toshiba Machine Co., Ltd., the composition was subjected to a transfer pressure of 0.5 MPa, a transfer time of 30 seconds, and an exposure dose of 1 J / cm.2 A transfer test was carried out under a vacuum atmosphere of 200 Pa, and the transferability and filling property of the fine pattern were evaluated according to the following criteria. Good: Transfer pattern filling rate is 95% or more Defective: The filling rate of the transfer pattern is less than 95%. The filling rate of the transferred pattern was determined by forming a 70 nm line & space pattern, and then observing the cross-sectional SEM image of the pattern, and determining the ratio of the pattern that was transferred without being chipped from the mold shape. The mold used was a standard film mold LSP70-140 (70 nm Line & Space) manufactured by Soken Chemical Industries, Ltd.

[0102] [Refractive index] The photocurable composition was spin-coated on a silicon substrate to a thickness of 600 nm, and then pre-baked at 100° C. for 1 minute. The composition was then exposed to light at a dose of 1 J / cm 2 using an imprinting device ST-200 manufactured by Toshiba Machine Co., Ltd. 2 A photocuring treatment was carried out under vacuum at 200 Pa to obtain a cured film. The refractive index of the resulting cured film was measured at a wavelength of 530 nm using a spectroscopic ellipsometer M2000 manufactured by JA Woollam.

[0103] [Hayes] The photocurable composition was spin-coated on an Eagle XG glass substrate so as to form a cured film having a thickness of 600 nm. Then, the substrate was pre-baked at 100° C. for 1 minute, and exposed to light at a dose of 1 J / cm using an imprinting device ST-200 manufactured by Toshiba Machine Co., Ltd. 2 A photocuring treatment was carried out under vacuum at 200 Pa to obtain a cured film. The haze of the resulting 600 nm thick cured film was measured using a haze meter COH7700 manufactured by Nippon Denshoku Industries Co., Ltd. with an illumination C light source (380 to 780 nm) in accordance with ASTM D1003.

[0104] [Table 3]

[0105] [Table 4]

[0106] From the results in Tables 3 and 4, the photocurable compositions of Examples 1 to 12 to which the present invention was applied had good imprint transferability and a high refractive index of 1.70 or more. In addition, the haze value was reduced to 0.1% or less. On the other hand, the photocurable compositions of Comparative Examples 1 to 16 were inferior in at least one of the imprint transferability, refractive index, and haze. From these results, it was confirmed that the photocurable compositions of the examples have good fine pattern transferability during pattern formation, and that the cured products can have reduced haze and a high refractive index in the visible light range. [Explanation of symbols]

[0107] 1. Substrate, 2. Photocurable film, 3. Mold

Claims

1. Component (X): metal oxide nanoparticles; Component (R): an unsaturated acid metal salt, Component (B): a photopolymerizable compound (excluding those corresponding to the component (R) above), Component (C): a photoradical polymerization initiator; A photocurable composition comprising: The component (X) is at least one kind of metal oxide nanoparticles selected from the group consisting of titania nanoparticles having a volume average primary particle diameter of 1 to 60 nm and zirconia nanoparticles having a volume average primary particle diameter of 1 to 60 nm, The photocurable composition has a content of the component (X) of 50 to 80 parts by mass relative to 100 parts by mass of the total content of the component (X), the component (R), and the component (B).

2. Component (X): metal oxide nanoparticles, Component (R): an unsaturated acid metal salt, Component (B): a photopolymerizable compound (excluding those corresponding to the component (R) above), Component (C): a photoradical polymerization initiator; A photocurable composition comprising: The component (X) is at least one kind of metal oxide nanoparticles selected from the group consisting of titania nanoparticles having a volume average primary particle diameter of 1 to 60 nm and zirconia nanoparticles having a volume average primary particle diameter of 1 to 60 nm, With respect to 100 parts by mass of the total content of the (X) component, the (R) component, and the (B) component, The content of the (R) component is 1 to 30 parts by mass, The photocurable composition has a content of the component (B) of 1 to 30 parts by mass.

3. Component (X): metal oxide nanoparticles, Component (R): an unsaturated acid metal salt, Component (B): a photopolymerizable compound (excluding those corresponding to the component (R) above), Component (C): a photoradical polymerization initiator; A photocurable composition comprising: The component (X) is at least one kind of metal oxide nanoparticles selected from the group consisting of titania nanoparticles having a volume average primary particle diameter of 1 to 60 nm and zirconia nanoparticles having a volume average primary particle diameter of 1 to 60 nm, A photocurable composition, wherein a cured film having a thickness of 600 nm formed using the photocurable composition has a haze value of 0.1% or less as measured in accordance with ASTM D1003.

4. Component (X): metal oxide nanoparticles, Component (R): an unsaturated acid metal salt, Component (B): a photopolymerizable compound (excluding those corresponding to the component (R) above), Component (C): a photoradical polymerization initiator; A photocurable composition comprising: The component (X) is at least one kind of metal oxide nanoparticles selected from the group consisting of titania nanoparticles having a volume average primary particle diameter of 1 to 60 nm and zirconia nanoparticles having a volume average primary particle diameter of 1 to 60 nm, The photocurable composition is for use in photoimprint lithography.

5. forming a photocurable film on a substrate using a photocurable composition; a step of pressing a mold having a concave-convex pattern against the photocurable film to transfer the concave-convex pattern to the photocurable film; a step of exposing the photocurable film to light while pressing the mold against the photocurable film to form a cured film; peeling the mold from the cured film; A pattern forming method comprising the steps of: The photocurable composition is Component (X): metal oxide nanoparticles; Component (R): an unsaturated acid metal salt, Component (B): a photopolymerizable compound (excluding those corresponding to the component (R) above), Component (C): a photoradical polymerization initiator; Contains The pattern forming method, wherein the component (X) is at least one type of metal oxide nanoparticles selected from the group consisting of titania nanoparticles having a volume average primary particle diameter of 1 to 60 nm and zirconia nanoparticles having a volume average primary particle diameter of 1 to 60 nm.

6. The pattern forming method described in claim 5, wherein a photocurable composition described in any one of claims 1 to 4 is used as the photocurable composition.

Citation Information

Patent Citations

  • Construction process of high-temperature-resistant and acid-resistant high-temperature uv texture

    CN114853352A

  • Water-based polishing agent composition

    JP2004231917A

  • Reactive and gel-free compositions for hybrid composite fabrication

    JP2005536617A

  • Resin composition for antistatic hard coat and its use

    JP2007070395A

  • Method for producing photo-setting material, photo-setting material and article

    JP2011012163A